Tricks To Master English Vocabulary Through Interactive Activities At The Puri Kasih Orphanage Tembilahan - Samsul Amri; Syafrizal Syafrizal; Maizarah Maizarah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2020)
English language skills are also often used as a requirement when they want to continue to a higher education level. However, it cannot be denied that the limited understanding of English vocabulary results in obstruction of language competence achievement. Therefore, this activity is a form of service to the community, especially as a form of implementation of the Tri Dharma obligations of higher education, which aims to help students at the Puri Kasih Tembilahan Orphanage to master English vocabulary quickly. The method used is Training of easy tricks to master English vocabulary through interactive activities. In this Community Service activity, several activities are carried out, namely: words puzzle, words matching, pictures, games, and watching short movies. The results of this Community Service activity showed that the participants gave a positive responses to this activity. They are also more courageous and motivated to use the vocabulary they have by participating in every activity they do. Furthermore, the initial test results showed 8.3% of participants in the Very Good category, 12.5% of participants in the Good category, 41.7% of participants in the Enough category, and 37.5% of participants in the Low category. Then, the final test results showed that 16.7% of participants were at the Very Good level, 25% of participants were at the Good level, 45.9% of participants were at the Enough level, and only 12.5% were at the Low level. This shows that interactive activities can help students at the Puri Kasih Tembilahan Orphanage more easily master English vocabulary.